Prevalence of bacterial vaginosis and associated risk factors in pregnant women receiving antenatal care at the Kumba Health District (KHD), Cameroon - Yiewou Marguerithe Kamga; John Palle Ngunde; Jane-Francis K. T. Akoachere (BMC, 2019)
Abstract Background Bacterial vaginosis (BV) is a common reproductive tract disorder in women of child bearing age, accounting for one third of vaginal infections. It is characterized by an increase in vaginal pH, decreased Lactobacilli, and overgrowth of facultative and anaerobic bacteria. Studies have consistently shown BV to be a risk factor for adverse obstetric and gynecological outcomes. BV is believed to play a critical role in the transmission of sexually transmitted infections. Its aetiology and risk factors are poorly understood. This study determined the prevalence and risk factors for BV among pregnant women in Kumba Health District (KHD) Cameroon to generate findings that could guide the design of interventions for prevention of infection and associated poor pregnancy outcomes. Methods A structured questionnaire was administered to 309 women seeking antenatal care (ANC) in three health facilities in KHD between May to July 2016, to capture data on demographic, gynecological and obstetric characteristics, and hygiene behavior. High vaginal swabs (HVS) collected from these women were gram stained, examined under a microscope and BV evaluated by Nugent scoring. Chi square (χ2) test was used to determine the relationship between BV and factors investigated. Statistical significance was set at p < 0.05. Results The prevalence of BV was 26.2%. Nine point 1 % of participants had a mixed infection with Candida. BV was higher (29.5%) in participants from the rural area (χ2 = 8.609. P = 0.014), those who did not use antibiotics (31.9%) prior to the study (χ2 = 12.893, P = 0.002) and women with no history of a genital tract infection (χ2 = 18.154, P = 0.001). There was a significant difference in prevalence with respect to gestation age (χ2 = 13.959, P = 0.007) with the highest occurring in women in the second trimester (31.7%). Women who practiced douching (χ2 = 23.935, P = 0.000) and those who did not wash pants with disinfectant (χ2 = 7.253, P = 0.027) had a high prevalence. Conclusion BV could be a health concern among pregnant women in study area. BV prevalence was affected by some hygiene behaviors, socio-demographic and clinical factors. Screening and treatment of positive cases during antenatal visits to prevent adverse outcomes, as well as education of women on vaginal hygiene is highly recommended.